PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK NO. 5 PADA HOTEL BOULEVARD - Muliadi, Halim Ellena; Alexander, Stanly W; Gamaliel, Hendrik (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Income statement is a report that describes the success of a company in carrying out its business activities. In this case, Boulevard Hotel in recording the income statement is still very simple not in accordance with applicable financial standards, namely Accounting Standard Non Publicly Accountable Entities (SAK ETAP). This study aims to make an income statement and describe and compare the results of the calculation of revenues, costs and profits based on SAK ETAP with the results of the calculation applied by Hotel Boulevard. This research is a descriptive qualitative research. The research method used is descriptive method that is describing the results of research in accordance with the facts found in the field. The results obtained indicate that Boulevard Hotel has not prepared financial reports in accordance with SAK ETAP No. 5.Â